Higher Protein Content From Nitrogen Fertilizer Application and Nutritive Value of Milled-Rice Protein - Eggum, Bjørn O.; Juliano, Bienvenido O. (Wiley, 1975)
An increase in milled‐rice protein content (N x 6.25) from 8.14 to 9.90% (at 12% moisture) in IR8 and from 9.90 to 13.0% in IR480–5–9 due to N fertiliser application had no significant effect on the lysine content of the protein and had little effect on the true digestibility, the biological value, and the net protein utilisation of the protein in growing rats.